Rigidity of heat-treated oriented isotactic polypropylene - Tsobkallo, Katherina; Tikhomirov, A.; Bozdogan, A.; Tshmel, A. (WILEY, 2006)
Uniaxially oriented commercial films of isotactic polypropylene were strained with ends keeping fixed and subjected to the heat treatment at temperatures from 50 to 200 degrees C. The rigidity of annealed samples was characterized by the value of tangent modulus, Et, determined graphically at the initial portions of stress-strain curves. The structural changes in the samples were studied with the help of the IR and low-frequency Raman spectroscopies. The smallest Et values were obtained for the low-strained films, while the tangent moduli measured for highly strained samples exceeded the value for the original (untreated) filin. The most prominent positive effect was achieved after annealing the samples at 90 degrees C. (c) 2006 Wiley Periodicals, Inc.
Keywords: Raman spectroscopy; mechanical properties; polyolefins; infrared spectroscopy; POLYETHYLENES; MORPHOLOGIES; Polymer Science